2022
DOI: 10.1039/d1cp03740d
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of the reactions of Br atoms with the xylenes: an experimental and theoretical study

Abstract: This work reports the temperature dependence of the rate coefficients for the reactions of atomic bromine with the xylenes that are determined experimentally and theoretically. The experiments were carried out...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 56 publications
(147 reference statements)
1
15
0
Order By: Relevance
“…The rate coefficients reported in the literature show that in most cases, the reactions of saturated VOCs with Cl atoms are faster than with OH radicals, which are in turn faster than the reactions with Br atoms. 35,44 This is also observed in part for title reactions, where the rate coefficients for the reaction (R2) are ∼35 times greater than those of reaction (R1). However, there is no available data for the reaction of TBC with Br atoms.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…The rate coefficients reported in the literature show that in most cases, the reactions of saturated VOCs with Cl atoms are faster than with OH radicals, which are in turn faster than the reactions with Br atoms. 35,44 This is also observed in part for title reactions, where the rate coefficients for the reaction (R2) are ∼35 times greater than those of reaction (R1). However, there is no available data for the reaction of TBC with Br atoms.…”
Section: Resultsmentioning
confidence: 61%
“…The stabilization of the complexes observed here is similar to the reactions of OH with other VOCs. 31–38 Stabilization of RCg is comparable to other H-bonded reactant complexes formed during the reactions of VOCs and OVOCs with OH radicals. Illés et al 31 reported the formation of H-bonded and van der Waals complexes with relative energies of 5.45 kcal mol −1 and 1.24 kcal mol −1 , respectively, in the reaction of tetrahydrofuran with OH radicals.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The results are used to elucidate the detailed mechanisms of these reactions. 1–6 Some of the more prominent reactive species that have been linked to atmospheric photo-oxidation of volatile organic compounds (VOCs) are OH, Cl and Br and the kinetics and mechanisms of many of these processes have been extensively reviewed. 7–12 These reviews lead to the generalization that the order of reactivity with a given VOC is roughly Cl > OH > Br.…”
Section: Introductionmentioning
confidence: 99%